RANCANG BANGUN SEPEDA LISTRIK TERINTEGRASI SISTEM KONTROL KECEPATAN, INTENSITAS CAHAYA, DAN PERINGATAN BAHAYA - Kenny Aldebaran Roberts; Erni Yudaningtyas; Raden Arief Setyawan (Jurnal Mahasiswa TEUB, 2023)
Electric bicycles in the modern era require useful features to make this mode of transportation a space for innovation to create systems that are more energy efficient, environmentally friendly, and safe for riders. In this study, several features were integrated, such as a light control system for bicycle lights, warning of danger using a buzzer, PID controller for bicycle motors, and supercapacitors for batteries. The research objective of a light control system based on power consumption efficiency is to produce a stable and accurate light intensity control response with an average error value of 5.887% and a recovery time value when given a disturbance of 1.032 seconds and consume a minimum of 2.784W of power and a maximum of 8.664 W. The purpose of hazard early warning research using a buzzer is to create an automatic warning system in accordance with Mamdani's fuzzy logic which in the testing process the output value of the PWM prototype is the same as the PWM output of the Fuzzy Matlab design. The aim of the PID controller research is to improve the performance of BLDC motors on bicycles, with targeted response characteristics of <14 s rise time, <15 rpm overshoot, <3 rpm steady-state error, and <1 s settling time. The PID system that has been tuned meets all target response characteristics besides settling time, with a rise time of 11.96 s, overshoot of 6.4 rpm, steady-state error of 2.71 rpm, and settling time of 1.17 s. Based on the experimental results, the supercapacitor battery system that has been implemented shows a decrease in the maximum output voltage from 42.2 V to 35.5 V and the peak battery current decreases from 19.1 A to 16.9 A, while the results of the output voltage and current experience a decrease in average power from 679.172 W to 586.508 W. Keywords: PID, Light, Buzzer, Supercapacitor